Spin regulation and control method of perovskite oxide and application of spin regulation and control method in electro-catalysis nitrate reduction reaction
The A-position hyperentropy strategy of LaCoO3 perovskite oxide regulates the spin state of the Co activity center, and prepares high-entropy perovskite oxides, which significantly improves the catalytic activity and Faraday efficiency of the electrocatalytic nitrate reduction reaction, and solves the problems of insufficient activity and low efficiency of traditional catalysts.
Patent Information
- Application Number
- CN202411598663.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-11
AI Technical Summary
The existing perovskite oxide catalysts have insufficient catalytic activity and poor Faraday efficiency in electrocatalytic nitrate reduction reaction, making it difficult to effectively promote the reaction rate and ammonia yield.
The spin state of the center of the B-position Co activity was regulated by the A-position hyperentropy strategy of LaCoO3 perovskite oxide, and a high-entropy perovskite oxide (La0.2Pr0.2Nd0.2Ba0.2Sr0.2)CoO3-δ was prepared, which significantly improved the catalytic activity.
The catalytic activity of perovskite oxides in electrocatalytic nitrate reduction reaction was significantly improved, with the highest Faraday efficiency reaching 76%, and the ammonia yield was 129μmol h-1mgcat.-1, solving the problems of insufficient activity and low efficiency of traditional catalysts.
Smart Images

Figure CN119591165A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new material preparation and catalytic technology, and specifically relates to a spin control method of a perovskite oxide and an application thereof in an electrocatalytic nitrate reduction reaction. Background Art
[0002] Electrocatalytic nitrate reduction reaction (eNRA) is of great significance in ammonia production and environmental governance, especially in addressing global nitrogen pollution and achieving sustainable ammonia synthesis. This reaction not only provides a key nitrogen source for agriculture, but also effectively removes nitrates from wastewater and alleviates the pressure of eutrophication of water bodies. Therefore, developing efficient and stable catalysts to achieve efficient conversion of eNRA is an important task in the current field of catalysis research. The eNRA process usually includes the adsorption of nitrate on the catalyst surface, a continuous deoxygenation process, and the subsequent step-by-step hydrogenation to form ammonia. Throughout the reaction process, the bonding interaction between metal sites and intermediates is affected by spin polarization. Spin-polarized metal active sites can induce quantum spin exchange interactions and promote spin electron transfer, thereby enhancing the electrocatalytic reaction. However, since the eNRA process involves eight electron transfer steps, multiple intermediates, huge energy requirements, and slow reaction kinetics, it is still very challenging to accelerate this process by controlling the spin state in the electrocatalyst.
[0003] At present, the role of the spin state of cobalt (Co) in the perovskite LaCoO3 in the oxygen evolution reaction and oxygen reduction reaction has been studied. g The electron orbital is unoccupied, and the Co atom of the original LaCoO3 is in a low spin state; g The occupation of the orbital means a higher spin state of the Co atom, which can improve the adsorption of oxygen-containing species on these central metal cations. The spin state of Co in LaCoO3 can be effectively adjusted by the A / B site doping strategy. Among them, A-site cation management helps to avoid the loss of active sites due to metal substitution, but it may lead to the aggregation or uneven distribution of cations in the material due to cation segregation. This will reduce the electrocatalytic activity and durability of the material, especially in traditional low-entropy perovskite oxides. High-entropy perovskite oxides have attracted widespread attention in the field of electrocatalysis due to their excellent properties such as high entropy characteristics, lattice distortion, slow diffusion and cocktail effect. It is worth noting that about 90% of the metal elements in the periodic table can exist stably in perovskite oxides, providing a broad space for material performance optimization. Although high-entropy perovskite oxides show excellent performance in electrocatalysis, their application in the field of eNRA has not been explored. At present, some low-entropy perovskite oxides have been used for eNRA, but their Faradaic efficiency and ammonia yield are low. Summary of the invention
[0004] In view of the above-mentioned problems, the purpose of the present invention is to provide a high-entropy perovskite oxide catalyst with a simple preparation process, high efficiency and stability. Compared with the traditional low-entropy perovskite oxide LaCoO3, it has a Co active center with a higher spin state, thereby exhibiting significantly improved eNRA catalytic activity, which helps to solve the problems of low catalytic rate and poor Faraday efficiency of perovskite oxides in the field of nitrate reduction to ammonia.
[0005] To achieve the above-mentioned purpose, the present invention provides a method for spin regulation of perovskite oxide, which regulates the spin state of the Co active center at the B site of LaCoO3 perovskite oxide through a high entropy strategy at the A site, thereby significantly improving the eNRA catalytic activity of the perovskite oxide.
[0006] The first object of the present invention is to provide a method for regulating the spin state of perovskite oxide by using a high entropy strategy at the A site, wherein the method is to prepare a high entropy perovskite oxide (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ .
[0007] In one embodiment of the present invention, the method for preparing the high entropy perovskite oxide comprises the following steps:
[0008] (1) adding lanthanum salt, praseodymium salt, neodymium salt, barium salt, strontium salt and cobalt salt into deionized water, stirring and dissolving the mixture to obtain a mixed solution; wherein the amount of lanthanum salt, praseodymium salt, neodymium salt, barium salt, strontium salt and cobalt salt is in a molar ratio of La:Pr:Nd:Ba:Sr:Co of 1:1:1:1:1:5;
[0009] (2) dissolving sodium hydroxide in deionized water, stirring and slowly adding the mixture to the mixture obtained in step (1) to form a suspension;
[0010] (3) transferring the suspension obtained in step (2) to a hydrothermal reactor for hydrothermal reaction, cooling to room temperature after the reaction is completed, washing the obtained product with deionized water and ethanol, and drying to obtain a powder;
[0011] (4) calcining the powder obtained in step (3) in air to obtain (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ High entropy perovskite oxide, named LPNBSC.
[0012] As a preferred embodiment of the present invention, the lanthanum salt in step (1) is lanthanum nitrate hexahydrate (La(NO3)3·6H2O), the praseodymium salt is praseodymium nitrate hexahydrate (Pr(NO3)3·6H2O), the neodymium salt is neodymium nitrate hexahydrate (Nd(NO3)3·6H2O), the barium salt is barium nitrate (Ba(NO3)2), the strontium salt is strontium nitrate (Sr(NO3)2), and the cobalt salt is cobalt nitrate hexahydrate (Co(NO3)2·6H2O).
[0013] As a preferred embodiment of the present invention, the total metal concentration in step (1) is 0.05-0.2 mol L -1 .
[0014] As a preferred embodiment of the present invention, the total metal concentration in step (1) is 0.133 mol L -1 .
[0015] As a preferred embodiment of the present invention, the amount of sodium hydroxide used in step (2) is 2-4 times the total molar number of metal, and the concentration of the sodium hydroxide solution is 0.1-0.8 mol L -1 Preferably, the amount of sodium hydroxide used is 3 times the total molar number of metal, and the concentration of the sodium hydroxide solution is 0.4 mol L -1 .
[0016] As a preferred embodiment of the present invention, the temperature of the hydrothermal reaction in step (3) is 160-200°C, and the reaction time is 6-18h. Preferably, the hydrothermal reaction temperature is 180°C, and the reaction time is 10h.
[0017] As a preferred embodiment of the present invention, the oven drying condition in step (3) is 60-100°C and the drying time is 5-10 hours. Preferably, the drying temperature is 70°C and the drying time is 5 hours.
[0018] As a preferred embodiment of the present invention, the calcination condition in step (4) is 700-900°C, and the calcination time is 4-8 hours. Preferably, the calcination temperature is 750°C, and the time is 5 hours.
[0019] The second object of the present invention is to provide (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ High entropy perovskite oxides.
[0020] As a preferred embodiment of the present invention, the high entropy perovskite oxide (La 0.2 Pr 0.2Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ It has a nearly spherical morphology, an average particle size of 50-70nm, and the Co element therein has a higher spin state.
[0021] The third object of the present invention is to provide the aforementioned (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ Application of high entropy perovskite oxides in electrocatalytic nitrate reduction to ammonia.
[0022] As a preferred embodiment of the present invention, the application is to convert (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ High entropy perovskite oxide was loaded on carbon paper as the working electrode with a loading of 0.54 mg cm -2 , using Ag / AgCl electrode as reference electrode and graphite rod as counter electrode, the electrocatalytic reduction of nitrate to produce ammonia was tested in an electrolyte containing 0.05M K2SO4 and 0.1M KNO3 using a standard three-electrode system.
[0023] The present invention also discloses a method of 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ Application of high entropy perovskite oxides in zinc-nitrate batteries.
[0024] As a preferred embodiment of the present invention, the cathode electrolyte of the zinc-nitrate battery is 0.5MKNO3 / 2MKCl, and the cathode is a carbon paper (1×1 cm 2 ); the electrolyte on the anode side was 2M KOH, the anode was zinc foil, and the two electrodes were separated by a Nafion 117 membrane. The loading amount of LPNBSC catalyst in the cathode was 1.0 mg cm -2 .
[0025] Beneficial effects:
[0026] 1. (La prepared by the present invention 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr0.2 )CoO 3-δ The Co element in the high-entropy perovskite oxide has a higher spin state, which solves the technical problems of insufficient catalytic activity and poor Faraday efficiency of traditional perovskite catalysts in the electrocatalytic nitrate reduction reaction. The high-entropy perovskite oxide prepared by the method of the present invention exhibits excellent catalytic activity, with the highest Faraday efficiency of 76%, and the corresponding ammonia yield of 129 μmol h -1 mg cat. -1 .
[0027] 2. Traditional perovskite catalysts often have low reaction rates and poor product selectivity due to the limitations of their electronic structure. The present invention prepares (LaCoO3) perovskite oxide by high entropy strategy at the A site. 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ High entropy perovskite oxides not only regulate the spin state of the B-site Co element, not only improve the electron availability of the material, but also optimize the distribution of active sites in the catalytic reaction, so that the reactants can be more effectively adsorbed on the catalyst surface, thereby significantly improving the catalytic performance. In addition, this spin regulation strategy provides new ideas for the application of perovskite materials in other electrocatalytic reactions, laying the foundation for more efficient ammonia production and environmental governance.
[0028] 3. The preparation process of the present invention is environmentally friendly and easy to operate, and is a green chemical preparation method.
[0029] 4. The high entropy perovskite in the present invention can be used to assemble zinc-nitrate batteries, which can not only generate clean energy but also recycle nitrate in wastewater into valuable ammonia. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The X-ray diffraction (XRD) patterns of the LaCoO3 material prepared in (a) Comparative Example 1 and the LPNBSC material prepared in (b) Example 1 of the present invention;
[0031] Figure 2 (a) low magnification and (b) atomic-level resolution high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images of the LPNBSC material prepared in Example 1 of the present invention;
[0032] Figure 3 is an energy dispersive X-ray spectroscopy (EDX) elemental mapping diagram of the LPNBSC material prepared in Example 1 of the present invention;
[0033] Figure 41 is a high-resolution X-ray photoelectron spectroscopy (XPS) graph of (a) Co 2p and (b) O 1s of the LPNBSC material prepared in Example 1 of the present invention and the LaCoO3 material prepared in Comparative Example 1;
[0034] Figure 5 It is an O k-edge X-ray absorption near edge spectrum (XANES) graph of the LPNBSC material prepared in Example 1 of the present invention and the LaCoO3 material prepared in Comparative Example 1;
[0035] Figure 6 Graphs of (a) yield and (b) Faraday efficiency of the LPNBSC material in the embodiment of the present invention and the LaCoO3 material in Comparative Example 2 as electrocatalysts for nitrate reduction to produce ammonia;
[0036] Figure 7 The LPNBSC material in Example 2 of the present invention is used as a nitrate reduction electrocatalyst for cycle testing at -0.7 V vs. RHE;
[0037] Figure 8 The discharge curve and power density curve of the zinc-nitrate battery assembled with the LPNBSC material in Example 3 of the present invention and the LaCoO3 material in Comparative Example 3 as the cathode. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] Sources of materials involved in the embodiments and comparative examples of the present invention:
[0040] La(NO3)3·6H2O, Pr(NO3)3·6H2O, Nd(NO3)3·6H2O, Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O and NaOH were purchased from Sigma-Aldrich.
[0041] Example 1
[0042] A method for preparing a high entropy perovskite oxide LPNBSC comprises the following specific preparation steps:
[0043] (1) Dissolve 173.2 mg of La(NO3)3·6H2O, 174.0 mg of Pr(NO3)3·6H2O, 175.3 mg of Nd(NO3)3·6H2O, 104.5 mg of Ba(NO3)2, 84.7 mg of Sr(NO3)2 and 582.1 mg of Co(NO3)2·6H2O in 30 mL of deionized water and stir until a clear solution is formed.
[0044] (2) Dissolve 480.0 mg of NaOH in 30 mL of deionized water, stir to dissolve, and then slowly add the mixture obtained in step (1) to form a suspension.
[0045] (3) The suspension was transferred to a 100 mL hydrothermal reactor and subjected to a hydrothermal reaction at 180°C for 10 hours. After the reaction was completed, the suspension was cooled to room temperature. The obtained product was washed with deionized water and ethanol, and then dried in an oven at 70°C for 5 hours.
[0046] (4) The dried powder was calcined in air at 750 °C for 5 h to obtain (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ High entropy perovskite oxide, named LPNBSC.
[0047] Example 2 Application of high entropy perovskite oxide LPNBSC in electrocatalytic nitrate reduction to ammonia
[0048] The eNRA test was performed using a CHI 660D electrochemical workstation in a standard three-electrode system. The Ag / AgCl electrode, graphite rod, and carbon paper loaded with LPNBSC catalyst were used as reference electrode, counter electrode, and working electrode, respectively, and the electrolyte was a 0.05M K2SO4 solution containing 0.1M KNO3. Before the eNRA measurement, the electrolyte was degassed by bubbling argon for 30 minutes. In the process of making the working electrode, 6mg of LPNBSC catalyst and 60μL of 5wt% Nafion solution were dispersed in 940μL of anhydrous ethanol. The mixture was ultrasonically treated to obtain a uniform ink. Subsequently, 90μL of the ink was applied to 1cm×1cm carbon paper. The electrode was then dried in argon at 80°C for 1h. The preparation method of the LPNBSC catalyst is the same as that in Example 1.
[0049] Example 3 Application of high entropy perovskite oxide LPNBSC in zinc-nitrate battery
[0050] Construction of zinc-nitrate battery: The cathode electrolyte is 0.5M KNO3 / 2M KCl, and the cathode is carbon paper (1×1cm 2 ); the electrolyte on the anode side is 2M KOH, the anode is zinc foil, and the two are separated by a Nafion 117 membrane. The loading amount of LPNBSC catalyst in the cathode is 1.0 mg cm -2 All battery data were recorded in a CHI 660D electrochemical workstation.
[0051] Comparative Example 1
[0052] Refer to Example 1, the only difference is that the mass of La(NO3)3·6H2O in Example 1 is adjusted to 866.0 mg, and Pr(NO3)3·6H2O, Nd(NO3)3·6H2O, Ba(NO3)2 and Sr(NO3)2 are not added. The rest are the same as Example 1. The low entropy perovskite oxide material finally obtained is recorded as LaCoO3.
[0053] Comparative Example 2 Application of LaCoO3 in the electrocatalytic nitrate reduction reaction to produce ammonia
[0054] The difference between Comparative Example 2 and Example 2 is that the 6 mg LPNBSC catalyst in Example 1 is adjusted to 6 mg LaCoO3 catalyst, and the preparation method of LaCoO3 catalyst is the same as that of Comparative Example 1.
[0055] Comparative Example 3
[0056] The difference between Comparative Example 3 and Example 3 is that the LPNBSC catalyst in Example 3 is adjusted to a LaCoO3 catalyst, and the preparation method of the LaCoO3 catalyst is the same as that of Comparative Example 1.
[0057] 1. The influence of high entropy strategy of A-site of LaCoO3 perovskite oxide on material structure
[0058] 1. XRD, HAADF-STEM, EDX, XPS and XAFS were used to characterize the prepared perovskite oxides. The XRD test results of LaCoO3 prepared in Comparative Example 1 and LPNBSC prepared in Example 1 are as follows: Figure 1 The HAADF-STEM test results of the LPNBSC prepared in Example 1 are shown as follows: Figure 2 The EDX element mapping diagrams of the LPNBSC prepared in Example 1 are shown as follows: Figure 3 The XPS graphs of the LPNBSC prepared in Example 1 and the LaCoO3 prepared in Comparative Example 1 are shown in Figure 4The XANES images of the LPNBSC material prepared in Example 1 and the LaCoO3 material prepared in Comparative Example 1 are shown in FIG. Figure 5 shown.
[0059] turn out:
[0060] (1) XRD test results show that: Figure 1 As shown, the XRD pattern of LaCoO3 prepared in Comparative Example 1 confirms that the LaCoO3 material has a single-phase hexagonal perovskite structure, and the LPNBSC material prepared in Example 1 is a single-phase cubic perovskite with higher symmetry. This phase transition caused by replacing lanthanum atoms in LaCoO3 with praseodymium, neodymium, barium and strontium shows that the increase in entropy can alleviate lattice strain and improve structural stability.
[0061] (2) The HAADF-STEM test results show that: Figure 2 As shown, LPNBSC has a nearly spherical morphology with an average particle size of 50-70nm ( Figure 2 a). Atomic-resolution HAADF-STEM images show that LPNBSC is projected along the
[100] direction. Due to the different average atomic numbers, two types of atomic columns can be distinguished. The measured interplanar spacing is and Corresponding to the (100) and (110) planes of cubic perovskite ( Figure 2 b).
[0062] (3) EDX test results show that: Figure 3 As shown, La, Pr, Nd, Ba, Sr, Co, and O elements are uniformly distributed in the LPNBSC nanoparticles, further confirming the successful preparation of the LPNBSC single-phase high-entropy perovskite oxide solid solution.
[0063] (4) The XPS test results show that: Figure 4 As shown in a, the high-resolution Co 2p XPS spectra show that Co coexists in both LaCoO3 and LPNBSC. 3+ and Co 2+ Among them, Co in LPNBSC 2+ / Co 3+ The intensity ratio is 0.83, which is significantly higher than 0.39 of LaCoO3, indicating that there is more Co in LPNBSC. 2+ In addition, compared with LaCoO3, the high-resolution O1s spectrum of LPNBSC shows a peak at 530.0 eV attributed to oxygen vacancies (OV) ( Figure 4 b), therefore, more Co will be generated in LPNBSC 2+ To maintain charge balance.
[0064] (5) XANES test results show that: Figure 5 As shown, in LaCoO3, a single peak at 530 eV is observed, indicating a completely empty e g In contrast, a new peak appears at 529 eV in LPNBSC, which is stronger than the peak at 530 eV. This transition indicates that the electrons are moving from t 2g Track transfer to e g Orbit.e g and t 2g This redistribution of electrons between energy levels creates partially unoccupied t 2g states, providing experimental evidence for the spin state transition caused by high entropy management at the A site.
[0065] 2. Effect of spin changes in perovskite oxides on the performance of nitrate reduction to ammonia
[0066] (1) eNRA performance test results of LPNBSC and LaCoO3 materials are shown in Figure 6 As shown in Figure 2, the LPNBSC in Example 2 reached 129 μmol h at -0.7 V. -1 mg cat. -1 The excellent ammonia yield is about 46 μmol h -1 mg cat. -1 ) Figure 6 a). In addition, the Faradaic efficiency of LPNBSC reaches a peak value of 76% at this potential, which is nearly twice that of LaCoO3 (42%) ( Figure 6 b) This result indicates that the high-spin Co ions in LPNBSC can significantly promote the electrocatalytic nitrate reduction to ammonia process compared with LaCoO3.
[0067] (2) Catalytic performance stability test of LPNBSC materials Figure 7 As shown, at the optimal reduction potential of -0.7 V vs. RHE, nitrate reduction tests were performed continuously for 10 times to evaluate the durability of the LPNBSC, and its ammonia yield and Faradaic efficiency remained stable during the cycle test.
[0068] 3. Performance test of zinc-nitrate battery
[0069] The performance tests of the zinc-nitrate battery based on LPNBSC and LaCoO3 in Example 3 and Comparative Example 3 are as follows: Figure 8 The discharge polarization and power density curves of the Zn-nitrate battery based on LPNBSC demonstrate that LPNBSC can deliver up to 15 mA cm at 0.45 V. -2The peak power density reaches 9.3mW cm at 0.29V. -2 , which is significantly higher than the 5.7 mW cm at 0.23 V of the LaCoO3-based zinc-nitrate battery. -2 The zinc-nitrate battery not only generates clean energy, but also recovers nitrate from wastewater into valuable ammonia.
Claims
1. A method for regulating the spin state of perovskite oxide by using an A-site high entropy strategy, characterized in that: The method is to prepare a high entropy perovskite oxide (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ , the preparation method of the high entropy perovskite oxide comprises the following steps: (1) adding lanthanum salt, praseodymium salt, neodymium salt, barium salt, strontium salt and cobalt salt into deionized water, stirring and dissolving the mixture to obtain a mixed solution; wherein the amount of lanthanum salt, praseodymium salt, neodymium salt, barium salt, strontium salt and cobalt salt is in a molar ratio of La:Pr:Nd:Ba:Sr:Co of 1:1:1:1:1:5; (2) dissolving sodium hydroxide in deionized water, stirring and slowly adding the mixture to the mixture obtained in step (1) to form a suspension; (3) transferring the suspension obtained in step (2) to a hydrothermal reactor for hydrothermal reaction, cooling to room temperature after the reaction is completed, washing the obtained product with deionized water and ethanol, and drying to obtain a powder; (4) calcining the powder obtained in step (3) in air to obtain (La 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ High entropy perovskite oxide, named LPNBSC.
2. The method according to claim 1, characterized in that In the step (1), the lanthanum salt is lanthanum nitrate hexahydrate (La(NO3)3·6H2O), the praseodymium salt is praseodymium nitrate hexahydrate (Pr(NO3)3·6H2O), the neodymium salt is neodymium nitrate hexahydrate (Nd(NO3)3·6H2O), the barium salt is barium nitrate (Ba(NO3)2), the strontium salt is strontium nitrate (Sr(NO3)2), and the cobalt salt is cobalt nitrate hexahydrate (Co(NO3)2·6H2O).
3. The method according to claim 1, characterized in that The total metal concentration in step (1) is 0.05-0.2 mol L -1 .
4. The method according to claim 1, characterized in that: The amount of sodium hydroxide used in step (2) is 2-4 times the total molar number of metal, and the concentration of the sodium hydroxide solution is 0.1-0.8 mol L -1 .
5. The method according to claim 1, characterized in that The temperature of the hydrothermal reaction in step (3) is 160-200° C., and the reaction time is 6-18 hours.
6. The method according to claim 1, characterized in that The oven drying condition in step (3) is 60-100° C. and the drying time is 5-10 hours.
7. The method according to claim 1, characterized in that The calcination conditions in step (4) are 700-900° C. and the calcination time is 4-8 hours.
8. (La prepared according to any one of claims 1 to 7 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ High entropy perovskite oxides.
9. The (La according to claim 8 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ Application of high entropy perovskite oxides in electrocatalytic nitrate reduction to ammonia.
10. The (La according to claim 8 0.2 Pr 0.2 Nd 0.2 Ba 0.2 Sr 0.2 )CoO 3-δ Application of high entropy perovskite oxides in zinc-nitrate batteries.
Citation Information
Cited By
High-entropy oxide stable noble metal monatomic catalyst as well as preparation method and application thereof
CN120174413A